Carica Papaya; A Paired and Alternative Therapy of Dengue Fever - Nesar, Shagufta; Omer, Kiran Rafiq; Rizvi, Sarwat; Ali, Aatka; Mumtaz, Tayyaba; Ali Usmani, Mohammad Shair (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2018)
The purpose f the study is to explore the prospective use of Carica papaya leaves extracts for Dengue fever that is a painful, debilitating mosquito-borne disease caused by dengue viruses. An estimated 390 million dengue infections occur worldwide each year, with about 96 million resulting in illness. It has been found at height in developing nations like India, Pakistan, Sri Lanka and Bangladesh. Mostly tropical areas have been reported infected. The disease is transmitted by an Aedes mosquito infected with a dengue virus; interestingly it is not transferred from person to person. Symptoms are mild to serious including hemorrhagic fever; a rare complication characterized by high fever, damage to lymph and blood vessels, bleeding from the nose and gums, enlargement of the liver, and failure of the circulatory system and it can cause the death. All the symptoms of disease are due to low platelets count that may become very low if not managed. Consequently the research reveals that juice of the leaves of the Carica papaya plant from the family Caricaceae help to increase the platelet levels. The present review is done to enlighten the theory of the management of dengue through this alternative therapy that can be implement along with conventional treatment. The covered researches in present study would raise and support the possibility of being, the remedy and significant alternative in the prospect.